Produção de tomate em substratos e em níveis de sombreamento em Tangará da Serra - MT - Santi, Adalberto (2014)
The current situation of the Brazilian economy provides efforts on increase of production at lower costs. Thus, it is important to characterize the microclimate changes due to the shade net employed as well as the management of tomato production in substrate from agro-industrial residues. Therefore, the present study aimed to: a) Evaluate the microclimatic changes caused by the use of shading netting in tomato cultivation; b) Evaluate the characteristics of the substrate and the biological productivity (yield and distribution of biomass); c) Evaluate the chemical quality of the substrates and the biometric variables of tomato six genotypes (‘Giuliana’, ‘Sweet Million’, ‘Cocktail Mascot’, ‘Sheila Victory’, ‘Sophia F3’ e ‘Débora Max’), grown under protected cultivation with different coverage types, rate of organic fertilizer, cultivation substrate ratios and under fertirrigation system with different ionic concentrations of nutrient solution. The study with tomato in substrate under protected cultivation in Tangará da Serra - MT, Brazil, was delimited by the matrix Baconian with 24 treatments and five replications in randomized block design, in the period of June to September of 2012, in which it was assessed: a) the tomato genotypes; b) covers of the protected cultivation; c) the effect of the proportion of filter cake mixed with carbonized rice hull forming the substrate; d) the organic fertilization with poultry litter added to the substrate; e) the effect of fertirrigation with different ionic concentrations of the nutrient solution for tomato. The data of solar radiation, temperature and relative humidity of ambient and the data of the substrate temperature were analyzed, as well as ,the productivity of fresh weight and assimilate partitioning of the leaves, rod clusters, fruit and root tomato. It was determined the chemical properties of the substrates and the tomato biometric variables: the number of total fruits, number of commercial fruits, number of unmarketable fruits, length, diameter and average weight of the fruit, as well as, the commercial production and total.It was observed that the protected cultivation reduces global solar radiation and throughout the day its value fluctuated, depending on the zenith angle of the sun and types of coverage. The increase of filter cake on the substrate increased the density of the substrate, the water retention capacity, pH, electrical conductivity and nutrient content of the substrates. The cultivar Sweet Million was the most productive.